1996
DOI: 10.2519/jospt.1996.23.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Toe Pressures Under the Foot While Dynamic Standing on One Foot in Healthy Subjects

Abstract: Static and dynamic standing balance are two of the most important variables assessed by rehabilitation clinicians when trying to determine whether patients are ready to assume more independence in their activities of daily living (3). The standing balance involves physiological as well as psychological characteristics of the individual ( 17). A quantitative, standardized test for standing balance, which also mimics the sensory conflicts often present in daily life, will be of great aid in the assessment of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…In standing, the great toe exerts more pressure than those of the five metatarsal heads and the heel, 1 with a pressure twice that of the total pressure of the other four toes. 2 During walking, as the great toe passively dorsiflexes, the longitudinal arch is raised, the rearfoot supinated, the leg externally rotated, and the plantar aponeurosis tensed. 3 This so-called windlass mechanism tenses the plantar fascia, thus forming a rigid lever for pushoff.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In standing, the great toe exerts more pressure than those of the five metatarsal heads and the heel, 1 with a pressure twice that of the total pressure of the other four toes. 2 During walking, as the great toe passively dorsiflexes, the longitudinal arch is raised, the rearfoot supinated, the leg externally rotated, and the plantar aponeurosis tensed. 3 This so-called windlass mechanism tenses the plantar fascia, thus forming a rigid lever for pushoff.…”
mentioning
confidence: 99%
“…Tanaka et al 2 tested subjects' single-leg stance on a moving platform and measured their sway responses and the peak pressure under the toes. Body sway was better correlated with peak anteroposterior sway than with lateral sway, and the peak pressure of the great toe was significantly greater than the sum of the peak values of the other four toes for both sides.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that, through both cutaneous feedback and muscle activity of the toe, the great toe and the forefoot play a very important role in maintaining balance during one-legged stance on a moveable or static platform with the eyes open or closed. 5,[34][35][36][37] The tactile sensitivity of the great toe decreases with age,38 and elderly people are less able to use the muscle of the great toe sufficiently to maintain balance when perturbations occur. 39 Plantar loading is mainly located in the anterior-medial areas of the foot during vibrations; this likely presents a strong challenge to the exertion of the great toe and subsequently has a training effect on the great toe muscles.…”
Section: Postural Response According To Vibration Condition: Posturalmentioning
confidence: 99%
“…Some studies suggest the foot pressure load size can affect the foot skin feedback to maintain body balance and the toe muscle activity, and the plantar pressure distribution has played a very important role in keeping balance. The 1st MTH area is one of the most sensitive areas on the foot sole, and the larger pressure located the anterior and medial foot regions may enhance the proprioceptive input from the 1st MTH (Tanaka et al, 1996). Therefore, it is expected that longterm BDJ exercise not only increases muscle strength but also enhance the proprioceptive and feedback of the anterior and medial plantar region, in order to aid in balance control.…”
Section: Pressure-time Integralmentioning
confidence: 99%
“…Shuqi Zhang (Zhang & Li, 2013) suggested that elderly people walking unstable mainly due to balance degenerated resulting from reduced foot proprioception, rather than muscle weakness. Therefore, training strength and proprioception of the GT may be better than single lower extremity strength training for physical therapy to help ameliorate the problem of balance in the geriatric population (Tanaka et al, 1996). In BDJ-second movements, body press often stimulated the GT and the 1st MTH region, so that the region skin of feedback transmission efficiency not diminished with increasing age.…”
Section: Peak Pressurementioning
confidence: 99%